BENTUK, FUNGSI DAN MAKNA MOTIF BATIK BUNGO DI KECAMATAN PELEPAT ILIR KABUPATEN MUARA BUNGO - KOKO SUSANTO, Drs. Erwin, M.Sn, Dra. Minarsih, M.Sn (Serupa The Journal of Art Education, 2015)
This article was written based on the fact indicating that Batik Bungo had not yet been recognized by Muaro Bungo people in particular and society in general. The purpose of this article was to describe the forms, function and meaning of Batik Bungo. This was a qualitative research which applied descriptive approach. The subject of the research was the owner of Batik galleries, PKK fellows, heads and staffs of Disperindagkop, Diskebpapora, Dekranasda and Muaro Bungo people. The data gathered was in the form of written note, recording, pictures and interview. It then was analyzed qualitatively. The result of the research depicted that the form of Batik Bungo motives were derived from stilation and distortion of Bungo Dani, Putri Malu, Bungo Bangkai Rami, Pakis Manggis, Daun Sirih Pinang and Rumah Adat. These motives were functioned as decoration on clothes and had social function to introduce typical batik of Bungo to people. The motives symbolized moral education and culture.Kata kunci: Bentuk, Funngsi, Makna